Analysis of White Feces Disease (WFD) caused by Vibrio sp. Bacteria and Dinoflagellata in Vannamei Shrimp (Litopenaeus vannamei) in Brackishwater Culture Pond - Moh. Awaludin Adam; Irawati Mei Widiastuti; Ernawati Ernawati; Achmad Yani Yayan; Era Insivitawati; Yuliana Yuliana; Rini Fitriasari Pakaya; Agoes Soegianto; Ach. Khumaidi (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchIndicated that white feces at Vanammei appeared along with the appearance of the disease besides its main trigger that is Vibrio sp.Increase the availability of carbon for photosynthesis process of phytoplankton.Clinical symptom of shrimp attacked by white feces disease is indicated by a change in intestine.AbstractShrimp disease that currently causes economic loss to shrimp farmers is White Feces Disease (WFD). This disease appeared due to several factors, such as poor pond management, unhealthy shrimp seed, and poor water quality which resulted in the appearance of Vibrio sp. bacteria and Dinoflagellate. This study aimed to analyze the cause of WFD outbreak in vannamei shrimp pond. The study method through direct experiment was applied in shrimp pond. Sampling was performed three times in each feeding tray to collect ten shrimps. Overall, sampling was performed twice a week. The Sample Survey Method was used to collect sample in this study. Result of study showed that clinical symptom was observed through changes in pattern and behavior of vannamei shrimp during culture. However, this observation resulted in insignificant data. Vannamei shrimp infected WFD tended to swim slower and often rose to the surface with body color turned red. Moreover, total organic matter (TOM) increased on week-7 along with the increasing growth of plankton, particularly from the Dinoflagellate group. However, bacterial growth of Vibrio sp. on week-7 was insignificant, yet many shrimps were found dead with white feces during that period. The result of analysis indicated that white feces disease was caused by Dinoflagellate besides the main trigger, namely, Vibrio sp.